Mental Health Improvement Through Prayer - Dina Rahma Fadlilah; Munaya Fauziah; Raghib Filhaq; Rohimi Zamzam; Dihartawan Dihartawan (Indonesian Journal of Islam and Public Health, 2022)
Mental health is an inner condition that is always in a calm, safe and peaceful state. According to WHO data (2016), there are about 35 million people affected by depression, 60 million people affected by bipolar, 21 million affected by schizophrenia, and 47.5 million affected by dementia. While the 2018 Baseline Health Survey (Riskesdas) data in Indonesia, 6.1% of the population aged 15 years experienced emotional disorders. This article is a type of literature review article or literature review by reviewing 5 journals published in 2013-2019 regarding mental health downloaded via http//:doaj.org. This article was written from April-July 2020. The teachings of Islam provide guidance to humans in facing trials and overcoming the difficulties of life, such as by being patient and praying, in the word of Allah SWT in the Qur'an which confirms as follows: "O you who believe, make patience and prayer as your helpers. verily Allah is with those who are patient." (Surat al-Baqarah verse 153). Islamic demands oblige humans to have good relations with Allah SWT, other people, as well as relationships with nature and the environment. So that it can help humans in treating their souls and preventing them from mental disorders and fostering mental health conditions.